An in vitro model of the tumor–lymphatic microenvironment with simultaneous transendothelial and luminal flows reveals mechanisms of flow enhanced invasion1. Issue 5 (11th May 2015) - Pisano, M.; Triacca, V.; Barbee, K. A.; Swartz, M. A.
<x xml:space="preserve">Abstract</x> This paper elucidates mechanisms of flow-mediated tumor invasion into lymphatics with a new in vitro model that integrates both interstitial and luminal flows.